Persistence and Movement of Fomesafen in Florida Strawberry Production. Issue 6 (2nd October 2018) - Reed, Thomas V.; Boyd, Nathan S.; Wilson, P. Christopher; Dittmar, Peter J.; Sharpe, Shaun M.
Abstract: Fomesafen is a protoporphyrinogen oxidase–inhibitor herbicide with an alternative mode of action that provides PRE weed control in strawberry [ Fragaria × ananassa (Weston) Duchesne ex Rozier (pro sp.) [ chiloensis × virginiana ]] produced in a plasticulture setting in Florida. Plasticulture mulch could decrease fomesafen dissipation and increase crop injury in rotational crops. Field experiments were conducted in Balm, FL, to investigate fomesafen persistence and movement in soil in Florida strawberry systems for the 2014/2015 and 2015/2016 production cycles. Treatments included fomesafen preplant at 0, 0.42, and 0.84 kg ai ha −1 . Soil samples were taken under the plastic from plots treated with fomesafen at 0.42 kg ha −1 throughout the production cycle. Fomesafen did not injure strawberry or decrease yield. Fomesafen concentration data for the 0.0- to 0.1-m soil depth were described using a three-parameter logistic function. The fomesafen 50% dissipation times were 37 and 47 d for the 2014/2015 and 2015/2016 production cycles, respectively. At the end of the study, fomesafen was last detected in the 0.0- to 0.1-m depth soil at 167 and 194 d after treatment in the 2014/2015 and 2015/2016 production cycles, respectively. Fomesafen concentration was less than 25 ppb on any sampling date for 0.1- to 0.2-m and 0.2- to 0.3-m depths. Fomesafen concentration decreased significantly after strawberry was transplanted and likely leached during overhead and drip irrigation used during the crop establishment.